Probing the Precession of the Inner Accretion Disk in Cygnus X-1 - Torres, Diego F. (2005)
We show that changes in the orientation of the inner accretion disk of Cyg X-1 affect the shape of the broad Fe Ká emission line emitted from this object, in such a way that eV-level spectral resolution observations (such as those that will be carried out by the Astro-E2 satellite) can be used to analyze the dynamics of the disk. We present here a potential diagnostic tool supported by numerical simulations by which a few observations of Cyg X-1, separated in time, can determine whether its accretion disk actually precesses, and if so, determine its period and precession angle. This approach could also be used for similar studies in other microquasar systems.